High risk of macrosomia in newborns of immigrant mothers - Mario De Curtis; Leonardo Villani; Arianna Polo (BMC, 2020)
Abstract Background In Italy live about 8.7% immigrants, which contribute to more than 15% of all deliveries taking place in Italy. We aimed to investigate whether newborns from high migratory pressure countries (HMPC) mothers have a different macrosomia and post-term pregnancy incidence compared to Italian newborns. Methods In this retrospective observational study, we analyzed data on 404.863 babies born between 2010 and 2017. Italian mothers delivered 309.658 (76.5%), HMPC mothers 88.179 (21.8%) and developed country (DC) mothers 7.026 (1.7%) babies. We analyzed the incidence of macrosomia and post term pregnancy. We estimated incidence rate (IR), unadjusted incidence rate ratio (IRR) and 95% confidence intervals (CIs) to evaluate the association between these perinatal parameters and the mother's region of birth. Results HMPC compared to Italian newborns showed a significantly higher incidence of birthweight > 4000 g (53.3‰ vs 39.1‰, p-value < 0.001; IRR 1.4, 95%CI = 1.36-1.45), birthweight ≥4500 g. (7.0‰ vs 3.8‰, p-value < 0.001; IRR 1.8, 95%CI = 1.67-2.0) and gestational age at birth > 41 weeks (19.9‰ vs 12.8‰, p-value < 0.001; IRR 1.55, 95%CI = 1.47-1.64). The macrosomia incidence between HPMC and Italian newborns was significantly increased at all gestational ages (Fig. 1), especially for mothers coming from Central Eastern Europe (121.79‰ vs 91.1‰, p-value< 0.001; IRR 1.34, 95%CI = 1.11-1.62). Conclusion In Italy immigrant status represents a risk factor for macrosomia and post-term birth, which could be related to socio-economic status and unfavorable life conditions of immigrant mothers during pregnancy.